2016
DOI: 10.1002/pits.21898
|View full text |Cite
|
Sign up to set email alerts
|

Collaboration for a Curriculum of Caring: The Zeitgeist Is Right

Abstract: Recent catastrophic school shootings have drawn worldwide attention to issues of gun control and mental health. In the wake of these tragedies, more and more schools have begun to adopt school-wide social and emotional learning (SEL) programs. However, we have few examples of what it looks like to integrate SEL skills into content curricula. What's more, teachers and support professionals are ill-equipped to engage in the collaborative work necessary to effectively integrate the teaching of SEL into academic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Students with strong social and emotional skills perform better in school both socially and academically, and these skills are predictive of future life success [38]. Over the last decade, there have been numerous calls for the teaching of social and emotional skills to be part of teacher training programs [4,[49][50][51]. As such, the authors again call for more awareness of and education for teachers in the embedding of targeted social skilling within the curriculum, particularly in the initial stages of the middle years of schooling when students can begin to exhibit early signs of disengagement [52].…”
Section: Discussionmentioning
confidence: 99%
“…Students with strong social and emotional skills perform better in school both socially and academically, and these skills are predictive of future life success [38]. Over the last decade, there have been numerous calls for the teaching of social and emotional skills to be part of teacher training programs [4,[49][50][51]. As such, the authors again call for more awareness of and education for teachers in the embedding of targeted social skilling within the curriculum, particularly in the initial stages of the middle years of schooling when students can begin to exhibit early signs of disengagement [52].…”
Section: Discussionmentioning
confidence: 99%
“…(For us, this meant sharing our relationship as former student–mentor and now colleagues.) Newman and Ingraham (2020, p. 15) talked about how they had collaborated “for several years prior to the study, including co‐facilitating the NASP Consultee‐centered Consultation Interest Group.” Smith and Gill Lopez (2016) who reported on an interdisciplinary collaboration to integrate social‐emotional learning in the classroom discussed their rapport with each other:
Emily and Paula shared a trusting relationship as colleagues, which was essential when opening their pedagogy and classrooms to each other. This relationship was also important for managing the anxiety in working outside one's expertise.
…”
Section: Key Findingsmentioning
confidence: 99%
“…While teachers can influence the caring development of their students by simply being a role more, the teachers could be more effective at teaching their student to be caring if they understand caring and how to foster caring growth in others (Narinasamy & Logeswaran, 2015). Some teacher preparation programs have integrated content for preparing teachers to incorporate caring lessons into their lesson plans (Smith & Gill Lopez, 2016). Smith and Gill Lopez (2016) investigated the outcome from assigning student teachers the task of creating lesson plans that integrated literacy standards and social-emotional learning standards.…”
Section: Caring In the Cuirriculummentioning
confidence: 99%
“…Some teacher preparation programs have integrated content for preparing teachers to incorporate caring lessons into their lesson plans (Smith & Gill Lopez, 2016). Smith and Gill Lopez (2016) investigated the outcome from assigning student teachers the task of creating lesson plans that integrated literacy standards and social-emotional learning standards. After observing the lessons and providing the student teachers critical feedback, Smith and Gill Lopez found that the student teachers were much more willing to embed social-emotional learning standards into their future lessons as teachers because of the benefits they saw from previous teachings.…”
Section: Caring In the Cuirriculummentioning
confidence: 99%